SOCIAL DEVELOPMENT OF ADOLESCENTS WITH AUTHORITARIAN PARENTS - Irfan Fahriza; Siti Cahyati; Alfaiz Alfaiz; Aisha Nadya (Study Program Guidance and Counseling, Univesitas Pendidik, 2022)
This study aims to determine the social development of adolescents in an authoritarian parenting style. Several previous studies have found that adolescents in families with authoritarian parenting tend to have negative social behaviour. This study uses the literature study method by analyzing several previous studies. The research steps are as follows: 1) looking for the topic to be studied, 2) prioritizing the literature to be studied, 3) making an abstraction, and 4) using a literature guide with a review style. The study's results found that authoritarian parenting tends to harm social development. It can be concluded that there is a significant relationship between parenting style and adolescent social development. Further research is recommended, especially for a student in boarding school who partially interacts with the parent.